Warisan Kerajaan Sriwijaya dan Majapahit dalam Kerangka Sejarah Asia Tenggara - Yohanis Kristianus Tampani; Maria Merciana Meo; Maria Avrianti Hoar; Maria Angela Un; Maria Renti Seran; Paskalia Gresandi Fatin; Augusta De Jesus Magalhaes (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2026)
This study aims to examine the historical legacy of the Sriwijaya and Majapahit Kingdoms in the context of the development of Southeast Asian civilization through a literature review approach. The study focuses on the contributions of both kingdoms in various aspects, including politics, economy, maritime activities, culture, education, and international diplomacy. Research data were obtained from primary and secondary sources, such as historical manuscripts, inscriptions, archaeological reports, and national and international scholarly publications. The findings indicate that the Sriwijaya Kingdom played a significant role as a major maritime power and an international center of Buddhist education that influenced intellectual networks across Asia. Meanwhile, the Majapahit Kingdom was prominent in developing systems of governance, law, and regional integration of the Nusantara through extensive political and trade networks. Both kingdoms not only shaped the social and cultural structures of their respective periods but also laid an important historical foundation for the formation of identity and regional dynamics in modern Southeast Asia. Therefore, the legacies of Sriwijaya and Majapahit remain highly relevant for understanding historical processes, regional integration, and the long-term development of Southeast Asian civilization.